Diversity and population structure of northern switchgrass as revealed through exome capture sequencing. (November 2015) - Evans, Joseph; Crisovan, Emily; Barry, Kerrie; Daum, Chris; Jenkins, Jerry; Kunde‐Ramamoorthy, Govindarajan; Nandety, Aruna; Ngan, Chew Yee; Vaillancourt, Brieanne; Wei, Chia‐Lin; Schmutz, Jeremy; Kaeppler, Shawn M.; et al.
Summary: Panicum virgatum L. (switchgrass) is a polyploid, perennial grass species that is native to North America, and is being developed as a future biofuel feedstock crop. Switchgrass is present primarily in two ecotypes: a northern upland ecotype, composed of tetraploid and octoploid accessions, and a southern lowland ecotype, composed of primarily tetraploid accessions. We employed high‐coverage exome capture sequencing ( 2.4 Tb) to genotype 537 individuals from 45 upland and 21 lowland populations. From these data, we identified 27 million single‐nucleotide polymorphisms (SNPs), of which 1 590 653 high‐confidence SNPs were used in downstream analyses of diversity within and between the populations. From the 66 populations, we identified five primary population groups within the upland and lowland ecotypes, a result that was further supported through genetic distance analysis. We identified conserved, ecotype‐restricted, non‐synonymous SNPs that are predicted to affect the protein function of CONSTANS ( CO ) and EARLY HEADING DATE 1 ( EHD1 ), key genes involved in flowering, which may contribute to the phenotypic differences between the two ecotypes. We also identified, relative to the near‐reference Kanlow population, 17 228 genes present in more copies than in the reference genome (up‐CNVs), 112 630 genes present in fewer copies than in the reference genome (down‐CNVs) and 14 430 presence/absence variants (PAVs), affecting a total of 9979 genes, including two upland‐specific CNV clusters. In total, 45 719 genes were affected by an SNP, CNV, or PAV across the panel, providing a firm foundation to identify functional variation associated with phenotypic traits of interest for biofuel feedstock production. Significance Statement: In order to develop switchgrass as a biofuel crop, it is important to understand the genetic and phenotypic diversity available in native populations. Here we used more than 2.4 Gb of sequence data from 66 divergent switchgrass populations to identify five population groups delineated by ploidy, ecotype, and geographic location, and found ecotype‐restricted sequence and structural variation in flowering time pathway genes. This sequence data provides a rich resource with which to identify functional variation for phenotypic traits.